QbD-guided phospholipid-tagged nanonized boswellic acid naturosomal delivery for effective rheumatoid arthritis treatment - Poonam Usapkar; Suprit Saoji; Pradnya Jagtap; Muniappan Ayyanar; Mohan Kalaskar; Nilambari Gurav; Sameer Nadaf; Satyendra Prasad; Damiki Laloo; Mohd Shahnawaz Khan; Rupesh Chikhale; Shailendra Gurav (Elsevier, 2024)
Studies have reported the potential role of Boswellic acids (BAs), bioactive pentacyclic triterpenes from Boswellia serrata (BS), in treating rheumatoid arthritis (RA). However, poor water solubility and limited oral absorption are restricting factors for its better therapeutic efficacy. Based on these assumptions, the current study aimed to develop naturosomal delivery of BAs to boost their extremely low bioavailability, colloidal stability, and water solubility. Nanonized naturosomes were developed and subsequently analyzed to show their physicochemical and functional features employing the quality-by-design approach. The solubility analysis of Boswellic acid naturosomes revealed a 16 times improvement in aqueous solubility compared to BS extract (BSE). The zeta potential and dynamic light scattering findings of BSE naturosomes (BSENs) have demonstrated their colloidal stability with regulated nano-size particles. Additionally, compared to BSE (⁓31%), in-vitro dissolution experiments showed that >99% of pentacyclic triterpenes were released from BSENs. Studies on ex-vivo permeation showed that BSENs' permeation (>79%) significantly improved over BSE's (⁓20%). In-vivo efficacy studies using CFA-prompted arthritis in rodents showed a critical expansion in body wt and an undeniable reduction in paw thickness, paw volume, and TNF-α treated with BSEN compared to the arthritis control and BSE-treated group. These findings suggest that BSENs can help treat RA drugs by demonstrating their efficacy in further clinical research to validate the significant improvements.